2018
DOI: 10.1186/s13550-017-0356-2
|View full text |Cite|
|
Sign up to set email alerts
|

Biokinetics, dosimetry, and radiation risk in infants after 99mTc-MAG3 scans

Abstract: Background: Renal scans are among the most frequent exams performed on infants and toddlers. Due to the young age, this patient group can be classified as a high-risk group with a higher probability for developing stochastic radiation effects compared to adults. As there are only limited data on biokinetics and dosimetry in this patient group, the aim of this study was to reassess the dosimetry and the associated radiation risk for infants undergoing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…In another study, Machado et al . used similar methods and calculated the absorbed doses in infant patients (1.6–11.0 months) which was 0.3 ± 0.2 mGy with injected activity of 17.4 MBq 99m Tc-MAG3, and ovarian dose per unit activity was 1.72 E-02 ± 1.14E-02 mGy/MBq [17]. The calculated absorbed doses from injected radiotracer in our study are comparable with these published studies.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In another study, Machado et al . used similar methods and calculated the absorbed doses in infant patients (1.6–11.0 months) which was 0.3 ± 0.2 mGy with injected activity of 17.4 MBq 99m Tc-MAG3, and ovarian dose per unit activity was 1.72 E-02 ± 1.14E-02 mGy/MBq [17]. The calculated absorbed doses from injected radiotracer in our study are comparable with these published studies.…”
Section: Discussionsupporting
confidence: 83%
“…NCINM 2.0 software was used in our study to calculate the internal gonadal dose. A limitation of this method is that NCINM 2.0 is based on the ICRP 80 publication which only provides biokinetic data for pediatric patients 1 year of age and older (6,17). We applied biokinetic data of 1-year-old from NCINM 2.0 to the 0-year phantom in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified several calculation errors in the second and seventh paragraphs of the discussion section.…”
Section: Correction To: Ejnmmi Research (2018) 8:10 Https://doiorg/101186/s13550-017-0356-2mentioning
confidence: 99%
“…Diethylenetriamine pentaacetic acid (DTPA) renal scan is a procedure which involves minimal but some radiation exposure. [ 5 6 ] Hence, how long to follow these patients with renal scan and minimum number of scans required for follow-up? We try to answer these questions through this prospective observational study.…”
Section: Introductionmentioning
confidence: 99%